Final year veterinary students' attitudes towards small animal dentistry: a questionnaire‐based survey. (7th August 2014) - Perry, R.
<x xml:space="preserve">Abstract</x> OBJECTIVES To investigate the attitudes of final year veterinary students towards small animal dentistry and to examine the teaching received in this subject, both at university and during extra‐mural studies. METHODS A cross‐sectional study of all UK final year veterinary students in 2012 was designed and used by a self‐administered Internet‐based questionnaire. RESULTS Six of seven universities participated with 188 student responses. All students felt that it was important or very important for a small animal practitioner to have a broad understanding of dentistry, and that orodental problems were common or very common in small animals. Almost all (99 · 5%) students perceived small animal dentistry as an important or very important subject. Less than 40% of students felt that the teaching had prepared them for entering practice. Over 50% reported that they neither felt confident in discussing orodental problems with clients nor in performing a detailed examination of the oral cavity. CLINICAL SIGNIFICANCE Dental problems are perceived by students as frequently encountered in small animal practice. The veterinary surgeon should be adequately trained to detect, diagnose and treat dental disease in small animals and many students feel that their current teaching is inadequate.